City Development Strategy for Can Tho - National Institute for Urban and Rural Planning (World Bank, Hanoi, 2017)
This report, City Development Strategy for Can Tho, was completed to portray the long term development strategy for the city of Can Tho in the Republic of Vietnam. The report states that within the next 20 years, Can Tho city will be a dynamic development for the whole Mekong Delta Region. As a centerpiece of the Mekong delta region, the southern part of Vietnam and the adjacent international regions. Can Tho will be a typical riverside city with a multi-center city system. It has the potential to become a center of hi-tech industry, trading, service and tourism; science and technology, healthcare and education-training, as well as a communication center for the entire Mekong delta.